Agricultural rituals in Sangam literature: சங்க இலக்கியப் பனுவலில் வேளாண்மைச் சடங்குகள் - K., Murugan (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2021)
The people of ancient Tamilnadu were practically farmers in nature. They have been heavily depended on agriculture, for which they have heavily relied upon the nature and its grace for their livelihood. Whenever they began their activities, there have been several rituals performed by the farmers to peace the mother nature. Though the practices were still carried out till now, they have changed over time, from mere ritual forms to the worship of deities and idols. Such formalization must have taken into consideration of various facts and factors. The article is aimed at exploring such inputs in detail. The Madurai Tamil Grand Dictionary gives many meanings for agricultural lands, such as "land means place, place, land, nation, land". Global anthropological life basis on land is explored in this article as well. Geologicism is a series of rituals that reveal agriculture came to be on the land and the rituals that follow. For this, the article has consulted various evidence from Tamil classical literatures. வேளாண்மைத் தொழில் செய்யும் மக்கள், இயற்கையை நம்பி வாழ்ந்து வந்தனர். வேளாண்மக்கள் இயற்கைக்காகச் செய்து வந்த சடங்குகள் கால மாற்றத்தில் தெய்வ வழிபாடாகவும், உருவ வழிபாடாகவும் மாற்றம் பெற்றன. “நிலம் என்பதற்கு இடம், தலம், நானிலம், தேசம், பூமி”[1] என்னும் பல பொருள்களாகத் தருகிறது மதுரைத் தமிழ் பேரகராதி. நிலம் என்பதன் அடிப்படையில் அமைந்த உலகமானுடவியல் வாழ்க்கை ஆராயப்படுகின்றது. நிலத்தில் எவ்வாறு வேளாண்மைகள் உண்டாயின என்றும், அதனைத் தொடர்ந்து சடங்கியல் வாயிலாக நிலவுலகியல் மக்களின் வாழ்வியலில் புலப்படுத்த சங்கிலித் தொடராக அமையப் பெறுகிறது. அதில் உள்ள சடங்குகள் அனைத்தும் இயற்கை சார்ந்தே உள்ளதனைச் சங்கநூல்கள் வாயிலாக அறிய முடிகிறது.